The steal - Bowden, Mark, 1951-; Teague, Matthew (Journalist) (New York : Atlantic Monthly Press, 2022)
"In the sixty-four days between November 3 and January 6, President Donald Trump and his allies fought to reverse the outcome of the vote. Focusing on six states--Arizona, Georgia, Michigan, Nevada, Pennsylvania, and Wisconsin-- Trump's supporters claimed widespread voter fraud. It was not a well-orchestrated matter. There was no guiding genius pulling the strings in key states for the defeated Donald Trump. In the weeks after the election, in counties and precincts all over the country, many local Republican officials and even Trump's own campaign workers washed their hands of his increasingly unhinged allegations of fraud. But there was no shortage of people willing to take up the fight. Urged on by Trump and his coterie of advocates, lawyers, and media propagandists, true believers turned on their colleagues, friends, and neighbors-- even those in their own party--to accuse them of rigging the election. The real story of the insurrection began months before Trump's mob attacked the US Capitol on January 6, 2021. That riot was the desperate final act, emblematic of the clumsy, failed movement Trump had been building for years. It began in cities and small towns all over America on election day, November 3, 2020. Working with a team of researchers and reporters, Bowden and Teague uncover never-before-told accounts from the election officials fighting to do their jobs amid outlandish claims and threats to themselves, their colleagues, and their families. The Steal is an engaging, in-depth report on what happened during those crucial nine weeks and a portrait of the heroic individuals who did their duty and stood firm against the unprecedented, sustained attack on our election system to ensure that every legal vote was counted and the will of the people prevailed."--Provided by publisher.
1. Election day -- 2. The count -- 3. The blunderbuss strategy -- 4. Pressure -- 5. The popular front -- 6. Epilogue -- Appendixes : A. List of House members who objected to certifying the Electoral College results -- B. List of Senators who objected to certifying the Electoral College results -- C. Guide to the lawsuits filed to challenge the election results.
Includes bibliographical references (pages 269-300).
110671
Keywords: View point -- Democrat Party; View point -- Liberal; President. -- United States -- Election -- 2020.; Elections -- United States -- History; History